COMPUTED TOMOGRAPHIC IDENTIFICATION OF DYSPLASIA AND PROGRESSION OF OSTEOARTHRITIS IN DOG ELBOWS PREVIOUSLY ASSIGNED OFA GRADES 0 AND 1. Issue 5 (16th May 2014) - Kunst, Chelsea M.; Pease, Anthony P.; Nelson, Nathan C.; Habing, Greg; Ballegeer, Elizabeth A.
<x xml:space="preserve">Abstract</x> Elbow dysplasia is a heritable disease that is a common cause of lameness and progressive elbow osteoarthritis in young large breed dogs. The Orthopedic Foundation for Animals (OFA) screens elbow radiographs, and assigns grades 0–3 based on presence and severity of bony proliferation on the anconeal process. Grade 1 is assigned when less than 3 mm is present and considered positive for dysplasia. We investigated the incidence of elbow dysplasia and progression of osteoarthritis in elbows with grades 0 and 1 in 46 elbows screened at least 1 year previously, using CT as a gold standard and with the addition of CT absorptiometry. The incidence of dysplasia based on CT was 62% in grade 0, and 75% in grade 1 elbows, all of which had medial coronoid disease. Progressive osteoarthritis at recheck was consistent with elbow dysplasia. The sensitivity and specificity of the OFA grade for elbow dysplasia compared to CT findings was 75% and 38%, respectively. Increased bone mineral density of the medial coronoid process as characterized by osteoabsorptiometry warrants further investigation with respect to elbow dysplasia. Proliferation on the anconeal process without CT evidence of dysplasia or osteoarthritis was present in 20% of the elbows, and is theorized to be an anatomic variant or enthesopathy of the olecranon ligament/synovium. Results of our study suggest that the "anconeal bump" used for elbow screening by the OFA is a relatively insensitive characteristic, and support the use of CT for identifying additional characteristics of elbow dysplasia.